IMPLEMENTASI PASAL 185 KHI TENTANG AHLI WARIS PENGGANTI (PLAATSVERVULLING) DI PENGADILAN AGAMA BANYUWANGI - Arif Hariyanto; Umla’ul Nikmah (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2020)
The issue of inheritance is often a cause of chaos and conflict in various parts of the world. Inheritance problems can occur from determining heirs or how to distribute the inheritance. And the solutions are sometimes simple (mutually voluntary) and not infrequently some are complicated so that the Religious Court judges participate in helping to solve it fairly. To facilitate understanding in this study, researchers used qualitative research methods. By multiplying the data sources from various literatures relating to the distribution of inheritance. The data obtained by researchers in the field included interviews with lawyers, judges and clerks at the Banyuwangi Religious Court to determine the implementation of Article 185 KHI. In addition, the data collection techniques were carried out by researchers by means of interviews, observation and documentation. In this study, the presence of researchers is also very important because researchers are human instruments as well as data collectors. From the results of the research that the researchers obtained, it can be concluded that firstly, the implementation of Article 185 of the KHI regarding the replacement heir is the person who gets the inheritance to replace the real heir because he died earlier than the heir. The concept of a substitute heir is not only on the up and down path, but can also be implemented on a sideways route. And the share of the successor heir is not more than the share of the heir which is equal to him and who is replaced. Second, the decision of the Banyuwangi Religious Court judge number 2659 / Pdt.G / 2016 / PA.Bwi which gives portions to sons and daughters of sisters (nephews) can be justified under Islamic law. Because the successor heir is related to lafadz al-mawaali in the verse 33 of Surah An-Nisa '. However, the existence of a part of the mandatory will that is given to one of the successor heirs needs to be considered. Because the judge's ijtihad as outlined in the decision as jurisprudence is applied meaning casuistic, the judge also needs to pay attention to justice. It is better if the replacement heir with the status of an adopted child is given only one part. Meanwhile, the other part is given to other relatives based on an agreement voluntarily, not on a predetermined group of heirs Keywords: ,,